STUDENTS PERCEPTION ON IMPLEMENTATION OF INTERPROFESSIONAL EDUCATION - Multazam Fahreza Chandra; Laila Isrona; Emilzon Taslim; Ilmiawati Ilmiawati (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2021)
Background: Collaboration between health professionals is needed to improve health services. The collaboration can be applied to the education system through the Interprofessional Education (IPE) concept. This study aimed to examine students’ perception on the IPE implementation.Methods: This was a descriptive study using cross-sectional method. The study sample were 300 undergraduate students in Medical Faculty Andalas University (MFAU). It consisted of 190 medical students, 72 psychology students, and 38 midwifery students. The sample was determined by proportionate stratified random sampling method. The research instrument used was Interdisciplinary Education Perception Scale (IEPS) questionnaire.Results:     The    252    students    (84%)     showed    positive    perception    on    IPE implementation. The highest percentage (90%) of the component of perception was actual cooperation and the component of understanding of others’ profession had the lowest percentage (51%). Midwifery students had the highest percentage of perception (92.1%), while the lowest percentage of perception was showed by psychology students (72.2%). The perception tended to increase in perception from first-year (85.7%) to second-year (89.9%) and declined in third-year students (76%).Conclusion: Students of MFAU having a good perception on the IPE implementation. However, there is a lack of understanding of others’ profession that needs to be addressed and improved.